PERKEMBANGAN LANSIA PENDERITA HIPERTENSI SETELAH DIBERIKAN TERAPI KOMPLEMENTER TOTOK PUNGGUNG DI DESA BANJARSARI KECAMATAN SUMBERASIH KABUPATEN PROBOLINGGO - Lucia Retnowati; Mega Silvia; Kasiati (HOSPITAL MAJAPAHIT : JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO, 2024)
The increase in elderly people with hypertension that is not balanced with hypertension control results in complications. Treatment of hypertension can be done with nonpharmacological methods such as back acupressure. However, subject knowledge about back acupressure is still lacking, this is unfortunate if it is not applied as an alternative to hypertension control so that health status The elderly are less than optimal. The purpose of this study was to identify the development of the elderly in terms of physical and emotional complaints after being given back acupressure therapy. This research is a case study with a descriptive research approach. Sampling using purposive sampling with 2 subjects. Data collection using interview techniques and observation sheets. Data is presented in the form of transcript tables, graphs, and narratives. Overall, it was found that the administration of back acupressure therapy for 2 weeks with 6 meetings experienced changes in blood pressure reduction, physical complaints and emotional complaints. It can be concluded that after the administration of acupressure therapy, the back has gradually decreased changes. Therefore, back acupressure can be done routinely and control a healthy lifestyle in daily life, so that health status becomes optimal.